Sejarah dan Dinamika Lembaga Pendidikan Islam di Nusantara: Surau, Meunasah, Pesantren, dan Madrasah - Ucik Saidatur Rohmah; Nur Hamid; Ifran Fuad Su'aedi (Social Science Academic, 2023)
Islamic educational institutions have existed since the time of the sultanates in the archipelago, which at that time were very popular among Indonesian people, and the most popular at that time were Islamic boarding schools. surau, dayah, meunasah, pesantren and madrasah. The history of educational institutions in the archipelago is very long, so the purpose of this research is to describe the history and dynamics of Islamic educational institutions in the archipelago, starting from surau, maunasah, pesantren and madrasah. The development of Islamic educational institutions is the impact of changes in people's behavior. Are Islamic institutions, one of which are Islamic Boarding Schools and Madrasas, becoming Islamic educational institutions that continue to exist or are there other models of educational institutions that are more accommodating to the civilization and culture of the Islamic world.